Pengaruh Harga, Kualitas Produk, dan Word Of Mouth (WOM) Atau Testimoni Konsumen Terhadap Keputusan Pembelian Pada Rumah Produksi Tia Sprei - Rizqika Solekhah; Muhammad Syaifulloh; Ari Kristiana (Jurnal Projemen UNIPA, 2023)
This study was conducted to examine the effect of price, product quality, word of mouth (WOM) or consumer testimonials on purchasing decisions. The population in this study was the general public of Brebes Regency using Slovin formula obtained a total sample of 75 respondents. In this study, the technique used in data collection is the Probability sampling technique with sampling using simple random sampling techniques. This type of research is descriptive quantitative. The analysis methods used are descriptive statistics, validity tests, reality tests, classical assumption tests consisting of normality tests, multicolonicity tests, heteroscedasticity tests, and hypothesis tests consisting of T tests, F tests, voefficient of determination tests (R2), and multiple linear regression analysis. Based on the results of partial research, it can be concluded that: 1). Price has a positive and significant effect with the value of t calculated > t table, which is 2.067 > 0.227 and the value of sig. < 0.05 which is 0.042 < 0.05. 2). Product Quality has a positive and significant effect with the t-value of the table t-count > of the table, which is 4.354 > 0.227 and the sig value. < 0.05 which is 0.00 < 0.05. 3). Word of Mouth (WOM) has a positive and significant effect with the t-value of the table t-count > which is 2.238 > 0.227 and the value of sig. 0.028 < 0.05. The results of the study simultaneously with the F test stated that the variables price, product causality, and word of mouth (WOM) had a positive and significant effect with the value of f calculated > f table which is 7.158 > 2.50 and the value of sig. < 0.05 which is 0.00.